Management of Bleeding due to Vitamin K Deficiency in Neonates: A Case Report - Myggi Rizdwike Nanda (Archives of The Medicine and Case Reports, 2023)
Vitamin K deficiency bleeding (VKDB) is an uncommon and life-threatening bleeding condition in infancy. This study aimed to present a case of bleeding due to vitamin K deficiency in neonates. A 7-day-old male infant presented to an emergency department (ED) following bleeding from an umbilical stump for 3 hours upon arrival at the hospital. On examination of the general condition, the patient is in good health, responsive, conscious and active tonus. Physical examination revealed there were no petechiae, purpura, or ecchymoses. On the abdomen region, there was minimal bleeding in an umbilical area with periumbilical hemorrhagic crusting. Intense palpation revealed mild tenderness near the periumbilical area. When the umbilical area was palpated deeply, a thin, watery blood fluid oozed out. The results of routine blood laboratory examinations showed within normal limits (Hb 12 g/dL, leukocytes 6.9x103/Î¼L, and platelets 150x10Â³/Î¼L). This patient was diagnosed with bleeding due to vitamin K deficiency. The management given is in the form of a subcutaneous injection of vitamin K 10 mg for 3 days. After administration of the third injection, the patient's condition improves, and the umbilical hemorrhage subsides.